Factors Determining Housing Demand in Saudi Arabia - Al Obaid, Hussain Mohammed A. (International Journal of Economics and Financial Issues, 2020)
Against the backdrop of real estate development and rising prices, which affect the affordability of housing in Saudi Arabia, this study empirically estimates housing demand using time-series analysis from 1987 to 2016. To find the main factors affecting housing demand in Saudi Arabia, this study developed an econometric model with explanatory variables such as income level, housing prices, population growth rate, demand for loans, and consumer price index (CPI). The results show that demand for housing is inelastic with respect to price, income, and population growth rate; moreover, the price elasticity of demand is less than that of income and population growth rate, in absolute terms. A regression analysis suggests that the most significant factors that determine housing demand in Saudi Arabia are population growth rate, CPI and demand for housing loans. This study was conducted with a particular focus on the Saudi Arabian market and showed some surprising results, which are not consistent with popular economic theories. Keywords: Housing demand; Income elasticity; Price elasticity JEL Classifications: E31, E32, R21, R31 DOI: https://doi.org/10.32479/ijefi.10262